2013
DOI: 10.1002/pbc.24696
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of modified LMB-based therapy for children with ataxia-telangiectasia and advanced stage high grade mature B-cell malignancies

Abstract: Children with ataxia-telangiectasia (A-T) and cancer have a poorer prognosis due in part to increased treatment-related toxicity. We piloted a curative intent approach in five children with A-T who presented with advanced stage (III, n=2; IV, n=3) B-NHL (diffuse large B-cell lymphoma, n=4; Burkitt leukemia, n=1) using a modified LMB-based protocol. Two achieved sustained CCR (one, CCR at 6 years; one, pulmonary death after 3 years in CCR). Two died from toxicity during induction and 1 failed induction with pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…[5][6][7][8]10,16,22,46 Our analysis showed that while approximately 50% of AT patients died from therapy-related toxicity, death from NHL and therapy-related complications was evenly distributed among NBS patients. In comparison, the NHL-BFM SG reported on 37 patients with chromosomal instability syndromes (AT and NBS) with 5-year EFS rates of 48%±12% for 16 patients with ALL/T-LBL (relapse/progression n=2; SML n=2; treatment-related death n=2; alive n=10) and 51%±16% for 21 patients with mature B-cell NHL (relapse/progression n=2; SML n=2; treatment-related death n=1; dead from underlying disorder n=4; alive n=12).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…[5][6][7][8]10,16,22,46 Our analysis showed that while approximately 50% of AT patients died from therapy-related toxicity, death from NHL and therapy-related complications was evenly distributed among NBS patients. In comparison, the NHL-BFM SG reported on 37 patients with chromosomal instability syndromes (AT and NBS) with 5-year EFS rates of 48%±12% for 16 patients with ALL/T-LBL (relapse/progression n=2; SML n=2; treatment-related death n=2; alive n=10) and 51%±16% for 21 patients with mature B-cell NHL (relapse/progression n=2; SML n=2; treatment-related death n=1; dead from underlying disorder n=4; alive n=12).…”
mentioning
confidence: 97%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17]20,21 Although these patients seem to have an inferior prognosis and an increased risk of treatment-related toxicity and death compared to patients with lymphoid malignancies without a PID, curative therapies including allogeneic stem cell transplantation (allo-SCT) have been repeatedly reported. 5,6,10,11,15,16,22 Systematic data on the spectrum of common and rare pre-existing conditions associated with NHL in children and adolescents are scarce with respect to the type of the pre-existing conditions and the clinical characteristics and outcome of the associated NHL subtypes. Thus, the two largest childhood NHL consortia, the European Intergroup for Childhood NHL (EICNHL) and the international Berlin-Frankfurt-Münster (i-BFM) Study Group (SG), designed a retrospective multinational study to collect data on unselected types of pre-existing conditions among children and adolescents with NHL.…”
Section: Introductionmentioning
confidence: 99%
“…9 With risk of excess toxicities, treating malignancies in AT poses challenges. 4,10 There are no reports of T-PLL treatment in AT to our knowledge. We describe an adolescent AT patient with T-PLL harboring JAK3 mutations, and her response to standard and targeted therapy.…”
Section: Introductionmentioning
confidence: 99%
“…PET imaging in this trial could contribute to a better understanding of the neurological improvement at the cortical motor level in the A-T brain. It should be noted that although PET imaging has been used among young patients in clinical pilot studies, 228 PET poses a significant radioactive risk in A-T patients (reviewed in Sahama 15 (Chapter 2)), therefore to manage this risk,…”
Section: High-resolution T1 Structural Imagesmentioning
confidence: 99%
“…Lastly, MP2RAGE sequences in A-T can also be used to capture GM pathology in the spinal cord, a key aspect of the A-T neurodegenerative phenotype (reviewed in Sahamageneral patient work-up 228 and through PET and 18F-fluorodeoxyglucose (FDG) use where brain glucose metabolism, a marker of brain function, was measured in ten adult A-T patients. This study uncovered lower glucose metabolism in the A-T cerebellum compared to controls and asymptomatic relatives (siblings), and significant inter-subject metabolic variability in the cerebellar vermis and brain.…”
Section: High-resolution T1 Structural Imagesmentioning
confidence: 99%